2014
DOI: 10.1038/ncomms4337
|View full text |Cite
|
Sign up to set email alerts
|

Temporal identity transition from Purkinje cell progenitors to GABAergic interneuron progenitors in the cerebellum

Abstract: In the cerebellum, all GABAergic neurons are generated from the Ptf1a-expressing ventricular zone (Ptf1a domain). However, the machinery to produce different types of GABAergic neurons remains elusive. Here we show temporal regulation of distinct GABAergic neuron progenitors in the cerebellum. Within the Ptf1a domain at early stages, we find two subpopulations; dorsally and ventrally located progenitors that express Olig2 and Gsx1, respectively. Lineage tracing reveals the former are exclusively Purkinje cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 49 publications
6
115
1
Order By: Relevance
“…Among Ptf1a + ventricular zone precursors, Olig1/2 + and Gsx1 + precursor cells are commited to develop into Rorα + Purkinje cells and Pax2 + interneurons, respectively. Olig1/2 and Gsx1 mutually represses each other during this temporal transition (Seto et al, 2014 cKO cerebella was the decreased proliferation of granule precursor cells of the EGL. Granule precursor cells contribute to the proper cerebellar growth and shape up the foliation pattern throughout embryonic and early postnatal stages (Martinez et al, 2013;Zervas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among Ptf1a + ventricular zone precursors, Olig1/2 + and Gsx1 + precursor cells are commited to develop into Rorα + Purkinje cells and Pax2 + interneurons, respectively. Olig1/2 and Gsx1 mutually represses each other during this temporal transition (Seto et al, 2014 cKO cerebella was the decreased proliferation of granule precursor cells of the EGL. Granule precursor cells contribute to the proper cerebellar growth and shape up the foliation pattern throughout embryonic and early postnatal stages (Martinez et al, 2013;Zervas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing cerebellum, Purkinje cells are born in the ventricular zone of the fourth ventricle and migrate radially (Kapfhammer ; Roussel & Hatten ; Hoshino ; Seto et al . ), although a recent report has indicated that Purkinje cells that are generated at E10.5 in the posterior periventricular region of the lateral cerebellum migrate tangentially towards the anterior direction (Miyata et al . ) (Fig.…”
Section: Cdk5 In Brain Developmentmentioning
confidence: 99%
“…Previous studies reveal co‐expression of a number of bHLH transcription factors within the Ptf1a expression territory of the VZ (Zordan, Croci, Hawkes, & Consalez, ), suggesting mosaics of bHLH multiple transcription factor programs drive GABAergic cell‐type specificity. More recently, the bHLH transcription factor gene Olig2 and the homeobox transcription factor gene Gsx1 have been identified as key temporal regulators of VZ progenitor cell fate (Seto et al, ). Using gain‐ and loss‐of‐function mutations in mice, Seto et al () showed the switch from a Purkinje cell (PC) to inhibitory interneuron cell fate from the VZ is negatively regulated by Olig2 expression in the dorsal region and positively regulated by Gsx1 expression in the ventral region.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the bHLH transcription factor gene Olig2 and the homeobox transcription factor gene Gsx1 have been identified as key temporal regulators of VZ progenitor cell fate (Seto et al, ). Using gain‐ and loss‐of‐function mutations in mice, Seto et al () showed the switch from a Purkinje cell (PC) to inhibitory interneuron cell fate from the VZ is negatively regulated by Olig2 expression in the dorsal region and positively regulated by Gsx1 expression in the ventral region. During development, PC progenitors transition to become inhibitory interneuron progenitors spreading from ventral to dorsal (Seto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation